Case Study : Eco-Shop / Muhammad Najib Mohd Fadzli - Mohd Fadzli, Muhammad Najib (2020)
Eco-Shop Sdn Bhd is one of the leading Retail Chain Store and has 82 branches throughout Malaysia. Eco-Shop was established on 1 June 2003, the head office and warehouse is located in Jementah, Johor. The main business is selling convenience goods including food, daily products, household products, cosmetics, toys, stationary, hardware and so on. The price for each item is RM2.12 only. In addition, they have used the fully computerized system to organize and facilitate the logistic of warehouse management with branches and sales management in the branch. The company promised to provides quality service based on customer request, supplying of goods is not only convenient but well worth to satisfy the needs of each customer. For example, supply of the latest products and goods collocation more than 8,000 types of products. The slogan for their company is “Beli Sekali, Pasti Kembali.” Their company type is Small-Medium Enterprise.